Evaluating The Determinants For Access To Subsidised Mortgage Housing In Jos, Nigeria - Daniel, Maren Mallo (Penerbit Universiti Sains Malaysia, 2014)
Nigeria's subsidised mortgage system operates on the assumption that workers would subscribe to a scheme (National Housing Fund [NHF]) as a precondition for access to housing. The subsidised mortgages are limited in supply and the mechanism lacks efficiency and distributional equity. These issues are empirically examined in Jos. A survey was conducted among workers in 24 randomly selected organisations. A total of 543 questionnaires were administered and 410 were retrieved. Analysis employing Pearson's chi square indicates a low-level of participation and a lack of awareness about the NHF scheme. There are negative feelings about the arrangement, and for the entire sample, gender and employment characteristics were found to have statistically significant relationships with participation in the NHF scheme. However, access to subsidised mortgage is influenced only by gender and tier of government employment. It is concluded that participation in the NHF scheme is a necessary but not a sufficient condition for access to mortgages in Jos. These findings call for increased awareness about NHF and improved efficiency in its administration. As the study was limited to the city of Jos, the methodology could be used to corroborate the evidence in other Nigerian cities